Tagline Public Service Advertising Anniversary Bone (HJB) During the Covid-19 Pandemic R. Barthes Semiotics Analysis - Fatimah Fatimah (Palakka : Media and Islamic Communication, 2022)
This study aims to determine the meaning and ideology contained in the PSA tagline contained in twibonize and banners made by the Regional Government of Bone and society in general. The 690th and 691st HJB celebrations were different from the previous year in that year's HJB celebrations coincided with disasters that hit the world. Therefore, the celebration of HJB is mostly done virtually. This research belongs to the category of qualitative descriptive research by describing the 690th and 691st HJB PSA taglines. The data source is taken from the 690th and 691st HJB taglines. The data collection methods in this study were recording techniques and note-taking techniques. The data were analyzed using Roland Barthes' semiotic theory to find out the meaning and ideology contained in the tagline. The results showed that the ideology of the 690th HJB PSA tagline was “uddani bali uddani” (longing for longing). The message contained in the PSA is that the celebration of HJB during the covid-19 lockdown requires citizens not to gather and attend crowds so that what happens is longing for the HJB event. For Bone residents who are overseas cannot return home. While the 691st HJB's tagline is "ya tutu upe, ya capa ya cilaka" the translation is who is careful will be lucky or safe, who is negligent will be harmed". The tagline is very relevant to the new normal period of the covid-19 pandemic. The ideology contained is that every citizen, especially the residents of Bone, applies health protocols in all their activities. The principle of being careful "yes tutu" must be applied in order to be safe from the covid-19 virus. The ideology carried is an appeal to all members of the Bone community to always protect themselves, their families and the environment from the covid 19 pandemic.